ANALYSIS OF ENTREPRENEUR OPPORTUNITIES IN TOURIST POTENTIAL AND MANAGEMENT ENVIRONMENT OF THE SIANG MOUNTAIN SEKINYAK HAMLET - Veneranda Rini Hapsari; Usman; Dokman Marulitua Sitomorang (Department of Management - Institut Shanti Bhuana, 2020)
Abstract This study aims to find out entrepreneurial opportunities in the Sekinyak Hamlet aimed at improving the economy. This research method is qualitative, with case studies. The research location is in Lumar sub-district, Sekinyak Hamlet, Bengkayang Regency. The object of this research is the people in Sekinyak Hamlet. Information obtained through observation, interviews and documentation. The results of this study indicate that the Belimbing Village, Dusun Sekinyak fosters business opportunities for the local community, such as the sale of agricultural produce, culinary businesses and souvenirs. Keywords: entrepreneurial opportunities, tourism potential, environmental management Abstrak Penelitian ini bertujuan untuk mengetahui mengetahui peluang wirausaha yang ada di Dusun Sekinyak yang bertujuan dalam meningkatkan perekonomian. Metode penelitian ini merupakan kualitatif, dengan studi kasus. Lokasi penelitian berada di kecamatan Lumar, Dusun Sekinyak, Kabupaten Bengkayang. Objek dari penelitian ini adalah masyarakat di Dusun Sekinyak. Informasi yang diperoleh melalui observasi, wawancara dan dokumentasi. Hasil dari penelitian ini ini menunjukkan bahwa Desa Belimbing, Dusun Sekinyak menumbuhkan peluang usaha bagi masyarakat setempat, seperti usaha penjualan hasil bumi, usaha kuliner maupun souvenir. Kata kunci: peluang wirausaha, potensi wisata, pengelolaan lingkungan